(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
In the discourse of Indian maritime trade history, particular attention is often directed towards the Indian Oceanic aspect of maritime trade history. Through the Vasco da Gama route, the Portuguese surpassed interregional boundaries between Europe and Asia, directly establishing connections between the markets of India and Europe. Consequently, India became integrated into the global economic framework. The history of this commercial connection between Europe and India has been extensively discussed. Historians such as W.H. Moreland, Ashin Das Gupta, M.N. Pearson, L.F. Thomaz, Irfan Habib, Sanjay Subrahmanyam, Lakshmi Subramaniam, Sushil Chaudhury, and Thirthankar Roy have deliberated upon the history of Indian Oceanic maritime trade. However, some historians have approached the discussion of this trade history with a Eurocentric perspective, while others have analyzed it from an Asian or specifically Indian viewpoint. As a result, two main objectives have been identified in the discourse of Indian Oceanic maritime trade history (1600-1800): a. European merchants established dominance in Indian Oceanic maritime trade, and b. European merchants marginalized indigenous merchant communities in India by overshadowing their operations. This essay primarily focuses on the comparative analysis of the representation of indigenous merchants vis-à-vis European merchants in the discourse of Indian Oceanic maritime trade history during the period from 1600 to 1800. Several historians have demonstrated that indigenous merchants accounted for a significantly larger portion of trade than their European counterparts in Indian Oceanic maritime trade history. The essay also attempts to highlight the chapter of indigenous merchants in the maritime trade history.